Microbial community analysis in biotrickling filters treating isopropanol air emissions - Pérez, M Carmen (Environmental technology, 2013)
The evolution of the microbial community was analysed over one year in two biotrickling filters operating under intermittent feeding conditions and treating isopropanol emissions, a pollutant typically found in the flexography sector. Each reactor was packed with one media: plastic cross-flow-structured material or polypropylene rings. The communities were monitored by fluorescence in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE) analysis of the 16S rRNA region. After inoculation with activated sludge, the biotrickling filters were operated using inlet loads (ILs) from 20 to 65 g C m(-3) h(-1) and empty-bed residence times (EBRTs) from 14 to 160 s. Removal efficiencies higher than 80% were obtained with ILs up to 35 g C m(-3) h(-1) working at EBRTs as low as 24 s. There was an increase in the total percentage of the target domains of up to around 80% at the end of the experiment. Specifically, the Gammaproteobacteria domain group, which includes the well-known volatile organic compound (VOC)-degrading species such as Pseudomonas putida, showed a noticeable rise in the two biotrickling filters of 26% and 27%, respectively. DGGE pattern band analysis revealed a stable band of Pseudomonas putida in all the samples monitored, even in the lower diversity communities. In addition, at similar operational conditions, the biotrickling filter with a greater relative abundance of Pseudomonas sp. (19.2% vs. 8%) showed higher removal efficiency (90% vs. 79%). Results indicate the importance of undertaking a further in-depth study of the involved species in the biofiltration process and their specific function